Pengaruh Alat Pembayaran Non Tunai Terhadap Permintaan Uang Kartal Di Indonesia - Nada Effendi; Apridar Apridar (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The aim of the research is to evaluate the effect of using non-cash payment instruments on the demand for currency in Indonesia. Time series data is used in the time period 2009 to 2023 with monthly observations. The analysis approach uses the Error Correction Model (ECM) to assess the correlation between variables in the short and long term. The estimation results confirm that the use of ATM/debit cards has a positive and significant impact on the need for currency, both in the short and long term. In contrast, credit card use shows a negative and significant impact on the need for currency in both time periods. Meanwhile, the use of e-money does not have an impact in the short term, but has a positive impact in the long term on the need for paper money in Indonesia. Therefore, this research suggests that Bank Indonesia should encourage more use of electronic payment tools to encourage people to reduce the use of currency, and promote the concept of a society that uses less cash (less cash society).